Biosynthesis of bioactive tamarixetin in recombinant Escherichia coli. (5th July 2020) - Darsandhari, Sumangala; Dhakal, Dipesh; Shrestha, Biplav; Lee, Sanghun; Jung, Narae; Jung, Hye Jin; Sohng, Jae Kyung
Abstract: Tamarixetin, a monomethylated derivative of quercetin, has been reported to possess many important biological activities. In the present study, a whole cell biotransformation system was used for regiospecific methylation of quercetin to produce 4′‐ O ‐methylated quercetin (tamarixetin) using methyltransferase from Streptomyces sp. KCTC 0041BP in Escherichia coli Bl21 (DE3). Its production was enhanced by adding a plasmid containing S ‐adenosine‐l ‐methionine (SAM) synthase from E. coli K12 (MetK) with subsequent feeding of l ‐methionine and glycerol in the culture. The best condition produced ∼279 μM (88.2 mg/L) of tamarixetin. The biological activity of tamarixetin was tested and compared with quercetin, 7‐ O ‐methylated quercetin, and 3‐ O ‐methylated quercetin. Results showed that the growth of all tested cancer cell lines (AGS, B16F10, C6, and HeLa) were inhibited by tamarixetin more effectively than other methylated derivatives of quercetin or quercetin. Tamarixetin also exhibited the best antimelanogenic activity among all compounds tested. Abstract : Tamarixetin was produced by utilizing whole‐cell biotransformation system that was generated by using regiospecific methyltransferase from Streptomyces sp. KCTC in Escherichia coli. The anticancer and antimelanogenic activities of the tamarixetin were also evalauted.